(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the role of electronic payment methods in achieving a competitive advantage for Libyan banks. To achieve the study’s objectives, the descriptive-analytical method was used. The questionnaire was used as the main tool for collecting data and information related to the subject of the study, and the data obtained was analyzed using the statistical program (SPSS) to reach more accurate and objective results The study population consisted of a simple random sample of employees at Sahara Bank Main Branch, where (95) questionnaire forms were distributed, which is equal to the research sample, and (88) questionnaires were returned that were valid for statistical analysis, representing (92%) of the distributed questionnaires. The study reached several conclusions, the most important of which is: the existence of a statistically significant relationship at a significance level of (a ≥ 0.05) between the dimensions of electronic payment methods and the dimensions of competitive advantage and their ability to achieve competitive advantage for banks. Among the most important recommendations of the study was the necessity of treating electronic payment methods as a strategic resource among the various resources that banks possess, and preserving them to achieve a competitive advantage for the bank.